(untitled) (Majalah Kedokteran Bandung, 2021)
Refractive error is a condition in which the cornea and lens fail to focus the light, resulting in reduced visual efficiency. Twelve million children are experiencing refractive errors worldwide and uncorrected refractive errors in children have been reported to cause asthenopia. This study aimed to determine the association between the types of refractive errors and asthenopia in children. This cross-sectional study was conducted on 111 students aged 10-13 years old in a public elementary school in Indonesia, SDN Penjaringan 10, in 2019. A questionnaire was used to assess asthenopia and the Snellen Chart, trial frames, and trial lenses were used for refractive errors examination. It was demonstrated that 87.4% of respondents experienced asthenopia, and 53.2% of respondents suffered from uncorrected refractive errors, mostly due to myopia. Fisher’s exact test results showed an association between refractive errors and asthenopia (p=0.019) with all myopic students experienced asthenopia. However, there was no significant association between astigmatism and asthenopia (p=0.754). In conclusion, not all types of refractive errors are associated with asthenopia.